Development of a Bacteriophage Cocktail to Constrain the Emergence of Phage-Resistant Pseudomonas aeruginosa - Yang, Yuhui; Shen, Wei; Zhong, Qiu; Chen, Qian; He, Xuesong; Baker, Jonathon L.; Xiong, Kun; Jin, Xiaoling; Wang, Jing; Hu, Fuquan; Le, Shuai (Frontiers in Microbiology, 2020)
With the emergence of multidrug-resistant and extensively drug-resistant bacterial pathogens, phage therapy and other alternative or additional therapeutic modalities are receiving resurgent attention. One of the major obstacles in developing effective phage therapies is the evolution of phage resistance in the bacterial host. When Pseudomonas aeruginosa was infected with a phage that uses O-antigen as receptor, phage resistances typically achieved through single-site mutations in genes responsible for production of lipopolysaccharide, which resulted in the change or loss of O-antigen structure. In this study, a 5 phages cocktail was constructed to constrain the emergence of phage-resistant P. aeruginosa. The phages in the cocktail which expanded the range of susceptible hosts were selected by both screening a panel of phages, and phage training to generate mutant phages which overcame the evolved resistance of the host. The phage cocktail was effective against a diverse selection of clinical isolates of P. aeruginosa, and in the short-term constrained the appearance of the phage-resistant mutants that had beleaguered the effectiveness of single phage. Thus, this study provides an alternative strategy for designing phage cocktail and phage therapy.